Veterinary Diagnostic Practice and the Use of Rapid Tests in Antimicrobial Stewardship on UK Livestock Farms - Buller, Henry; Adam, Katie; Bard, Alison; Bruce, Ann; (Ray) Chan, Kin Wing; Hinchliffe, Stephen; Morgans, Lisa; Rees, Gwen; Reyher, Kristen K. (Frontiers in Veterinary Science, 2020)
In this paper we consider the shifting role, practice and context of veterinary diagnosis in addressing concerns over unnecessary or excessive antimicrobial medicine use in UK livestock farms. With growing policy and regulatory interest in diagnostic practices and technologies, coupled with an expanding focus on the development and deployment of new rapid and point-of-care on-farm diagnostic testing, this paper investigates current diagnostic practices amongst veterinarians working on dairy, pig and poultry farms in the UK and, more specifically, veterinarians’ use and perceptions of new and emerging rapid and point-of-care diagnostic tests. Drawing on a series of 32 semi-structured interviews with farm animal veterinarians across the three sectors, this paper examines the manner in which such tests are both used and anticipated in clinical farm animal veterinary practice and the possible impact rapid test technologies might have on broader farm animal health management and disease control. Analysis of the transcribed interviews reveals a number of complexities around the use of rapid and point-of-care diagnostic tests, notably with respect to the relative value of rapidity in test results, to the balance between detail and simplification in situations of multifaceted on-farm etiologies and to the shifting distribution of responsibilities in animal health care within contemporary food chains. The veterinarians in this study identified areas where new rapid and point-of-care tests would be of particular value to them in their clinical practice particularly in addressing concerns over inappropriate antimicrobial use in animal treatment. However, despite the considerable policy advocacy on rapid and point-of-care tests as key tools in shifting diagnostic practice and reducing unnecessary antimicrobial use, veterinarians in this study, while recognizing the potential future role of such tools and technologies, nonetheless viewed diagnosis practice as a far more complex process for which rapid tests might constitute only a part.